PENGARUH SISTEM PERPAJAKAN BAGI WPOP DAN KEPUASAN HIDUP TERHADAP KEPATUHAN PAJAK - Anisah, Siti; Venusita, Lintang (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to test whether there is an influence between the taxation system and life satisfaction on tax compliance. The population in this study were Individual Taxpayers (WPOP) in the city of Surabaya. The number of samples in this study was 400 respondents. The sampling technique used the purposive sampling method. The research method used is a quantitative method with data sources in the form of primary data, namely questionnaires filled out by respondents via gform and written and distributed via social media and visiting one of the KPP in Surabaya. The data was processed using SMART PLS by testing the inner model and outer model. The results of this study provide evidence that the taxation system and life satisfaction have a significant effect on tax compliance